The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3109/08982104.2016.1140182
|View full text |Cite
|
Sign up to set email alerts
|

Edge activators and a polycationic polymer enhance the formulation of porous voriconazole nanoagglomerate for the use as a dry powder inhaler

Abstract: The results suggest that using the combination of edge activators and diluted polycationic polymer solution provides porous voriconazole nanoagglomerates in a respirable range, which is proved successful in enhancing both the deposition and the dissolution of water insoluble-drugs in the lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The optimized TBN-NVS formulation exhibited a highly negative ζ potential (−31.17 ± 2.58 mV) indicating quality of dispersion. The negative charge on the surface of NVS might be owed to the presence of stearic acid that increased NVS stability in the aqueous phase (Salem et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized TBN-NVS formulation exhibited a highly negative ζ potential (−31.17 ± 2.58 mV) indicating quality of dispersion. The negative charge on the surface of NVS might be owed to the presence of stearic acid that increased NVS stability in the aqueous phase (Salem et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The total emitted dosage described as the entire amount of medication ejected from the mouthpiece and expressed based on the nominal emitted dosage that represents the initial amount of medication introduced in the device (Salem et al., 2016 ). The medication delivery mechanism was constructed in such manner analogous to that of a rat receiving the TBN-NVS suspension via endotracheal tube.…”
Section: Characterization Of Tbn-nvsmentioning
confidence: 99%
“…69 This smaller MMAD of improved SD/ P4 compared to improved SD/P6 (3.18 ± 0.29 µm) might guarantee deposition in the alveolar region. 70 It could be concluded that the use of curcumin-loaded proliposomes aerosol 71,72 might result in better lung deposition over the use of the pure powder suggestive for a future clinical bioequivalence test to consolidate this finding.…”
Section: Aerodynamic Particle Size Characterizationmentioning
confidence: 99%
“…In addition to the possibility of sustained-release, which facilitates patient adherence to fungal infection treatments, one of the goals of using nanotechnology is also related to improving the solubility of voriconazole in aqueous media, or allowing new routes of administration [212,213]. In order to provide new routes of administration for voriconazole besides the oral one, nanotechnology has been explored for ocular [54,214,215,216], pulmonary [53,217,218,219], and nail [220] distribution routes.…”
Section: Voriconazolementioning
confidence: 99%
“…Nanostructured systems have been used to increase flucytosine permeability in different tissues. Salem et al [217] incorporated flucytosine into gold nanoparticles to increase intraocular penetration and to evaluate the therapeutic efficacy of this topically applied formulation. In addition to intraocular permeation, Salem et al [240] used glutathione to increase flucytosine permeation through the blood-brain barrier, achieving a system with an average size of 100 nm and 70% drug release.…”
Section: Flucytosinementioning
confidence: 99%